Insulin pump therapy in children with type 1 diabetes: analysis of data from the SWEET registry - Szypowska, Agnieszka; Schwandt, Anke; Svensson, Jannet; Shalitin, Shlomit; Cardona-Hernandez, Roque; Forsander, Gun; Sundberg, Frida; De Beaufort, Carine; Maahs, David; Maffeis, Claudio; O'Riordan, Stephen M P; Krisane, Iveta Dzivite; et al. (Pediatric diabetes, 2016)
BACKGROUND: Intensified insulin delivery using multiple daily injections (MDI) or continuous subcutaneous insulin infusion (CSII) is recommended in children with type 1 diabetes (T1D) to achieve good metabolic control. OBJECTIVE: To examine the frequency of pump usage in T1D children treated in SWEET (Better control in Paediatric and Adolescent diabeteS: Working to crEate CEnTers of Reference) centers and to compare metabolic control between patients treated with CSII vs MDI. METHODS: This study included 16 570 T1D children participating in the SWEET prospective, multicenter, standardized diabetes patient registry. Datasets were aggregated over the most recent year of treatment for each patient. Data were collected until March 2016. To assess the organization of pump therapy a survey was carried out. RESULTS: Overall, 44.4% of T1D children were treated with CSII. The proportion of patients with pump usage varied between centers and decreased with increasing age compared with children treated with MDI. In a logistic regression analysis adjusting for age, gender and diabetes duration, the use of pump was associated with both: center size [odd ratio 1.51 (1.47-1.55), P < .0001) and the diabetes-related expenditure per capita [odd ratio 1.55 (1.49-1.61), P < .0001]. Linear regression analysis, adjusted for age, gender, and diabetes duration showed that both HbA1c and daily insulin dose (U/kg/d) remained decreased in children treated with CSII compared to MDI (P < .0001). CONCLUSIONS: Insulin pump therapy is offered by most Sweet centers. The differences between centers affect the frequency of use of modern technology. Despite the heterogeneity of centers, T1D children achieve relatively good metabolic control, especially those treated with insulin pumps and those of younger age.
Keywords: injekce; MDI; continuous subcutaneous insulin infusion; Female; Infant; dítě; předškolní dítě; ženské pohlaví; Adolescent; Registries; lidé; Blood Glucose; Injections; CSII; childhood diabetes; Diabetes Mellitus, Type 1; Male; kojenec; Child, Preschool; inzulinové infuzní systémy; Child; registrace; mužské pohlaví; multiple daily injections; krevní glukóza; mladiství; diabetes mellitus 1. typu; Insulin Infusion Systems; Humans